OPTIMIZATION OF TEAM QUIZ STRATEGY IN ISLAMIC RELIGIOUS AND CHARACTER EDUCATION LEARNING AT SMP NEGERI 2 PANYABUNGAN - Indah Permatasari; Syafri Martabe Rizka Nasution (Journal International Inspire Education Technology, 2025)
This research is motivated by the challenge of increasing students’ active participation in Islamic Religious and Character Education (PAI-BP) learning at the junior high school level, which impacts their understanding of the material and the development of collaborative skills. This study aims to examine the optimization of the team quiz strategy in PAI-BP learning, identify effective implementation steps, and analyze the supporting and inhibiting factors in its application. The research adopted a descriptive qualitative design with a purposive sample involving the school principal, 2 PAI-BP teachers, and 10 students at SMP Negeri 2 Panyabungan. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles and Huberman’s data analysis techniques with source triangulation to ensure data validity. Findings reveal that the optimization of the team quiz strategy was carried out through random grouping of students considering ability diversity, efficient time management, and clear role distribution within groups. The main supporting factors include full support from the school through regular socialization, teacher competence in designing innovative learning strategies, and high student enthusiasm for interactive learning. Identified obstacles include limited learning time and differences in understanding levels among students. This study concludes that the team quiz strategy plays a crucial role in increasing students’ active engagement, cooperation, and understanding of PAI-BP material. The research implications include a theoretical contribution to enriching active learning literature, particularly in PAI-BP subjects, and practical recommendations for teachers to implement random grouping, clear role division, and gradual implementation of team quizzes to overcome time limitations. This study also identifies opportunities for future research related to the development of technology-integrated team quiz models and their implementation in different learning contexts.